Laminated heat shrinkable film

The heat-shrinkable polyester film addresses the challenge of maintaining transparency and printing quality while minimizing wrinkles and air entrapment by incorporating specific properties such as heat shrinkage rate, surface roughness, and air drainage time, even at reduced thicknesses to minimize waste.

JP2025072584AActive Publication Date: 2025-05-09TOYOBO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2025019854
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-10-01
Filing Date
2025-02-10
Publication Date
2025-05-09
Estimated Expiration
2041-09-22

AI Technical Summary

Technical Problem

Existing heat-shrinkable polyester films face challenges in maintaining transparency and printing quality while minimizing wrinkles and air entrapment when rolled, especially when thinned to reduce waste.

Method used

A heat-shrinkable polyester film with specific properties, including a warm water heat shrinkage rate of 40% to 80% in the film width direction, a maximum protrusion height of 0.8 μm to 3.0 μm, an arithmetic average height of 0.03 μm to 0.2 μm, and an air drainage time of less than 14 seconds, is developed. The film is designed to maintain these properties even at a thickness of 15 μm to 50 μm.

Benefits of technology

The film achieves good air flow, winding quality, and resistance to wrinkles, while maintaining transparency and printing performance, thus addressing the environmental concern of reducing waste by minimizing film thickness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025072584000004
    Figure 2025072584000004
  • Figure 2025072584000001
    Figure 2025072584000001
  • Figure 2025072584000002
    Figure 2025072584000002
Patent Text Reader

Abstract

To provide a heat shrinkable polyester film in which film surface protrusion is made within a definite range so as to have a film roll having high heat shrinkage in a width direction that is a main shrinking direction and capable of obtaining a film roll with transparency, printability and excellent appearance.SOLUTION: A heat shrinkable polyester film characterized by satisfying the following requirements (1) to (5). (1) The hot water heat shrinkage rate when the film is immersed in hot water at 90°C for 10 seconds is between 40% and 80% in the film's width direction. (2) The hot water heat shrinkage rate when the film is immersed in hot water at 90°C for 10 seconds is between -5% and 10% in the film's length direction. (3) The maximum projection height Sp on at least one film surface is between 0.8 μm and 3.0 μm. (4) The arithmetic mean height Sa on at least one film surface is between 0.03 μm and 0.2 μm. (5) The air escape time between the front and back surfaces of the film is 14 seconds or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-shrinkable polyester film, and more particularly to a heat-shrinkable polyester film that is transparent, has few wrinkles when in roll form, and is suitable for processing such as printing, a heat-shrinkable label, and a packaging material. [Background technology]

[0002] In recent years, polyester-based heat-shrinkable films, which have high heat resistance, are easy to incinerate, and have excellent solvent resistance, have come to be widely used as shrink labels for applications such as label packaging, cap seals, and accumulated packaging that combine the protection of glass or plastic bottles and the like with product display, and the amount of these films used is tending to increase along with the increase in PET (polyethylene terephthalate) bottle containers, etc. Until now, thick heat-shrinkable films have been used as labels for covering PET bottles. However, heat-shrinkable films used for packaging become just waste after the contents have been used. In response to the growing environmental awareness of reducing waste as much as possible, film manufacturers are also trying to reduce the thickness of heat-shrinkable polyester films in order to reduce the thickness of labels. However, the inventors have found that reducing the thickness of the film reduces the stiffness of the film, and also makes it easier for air to get in when the film is wound into a roll, resulting in the problem of wrinkles occurring in the roll if the air cannot escape easily. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5240387 [Patent Document 2] JP 2020-117700 A Summary of the Invention [Problem to be solved by the invention]

[0004] A typical heat shrinkable film is uniaxially stretched, and has a high tensile breaking strength in the stretching direction, which is the main shrinkage direction, and a low tensile breaking strength in the non-shrinkage direction (the direction perpendicular to the main shrinkage direction). In contrast, in Patent Document 1, a heat shrinkable polyester film is biaxially stretched to increase the tensile breaking strength in both the longitudinal and transverse directions, thereby producing a film with high film strength. However, compared to the production method of a typical heat shrinkable film, there are problems such as the film production method being very complicated, the need for large equipment, and high initial investment costs. Furthermore, Patent Document 2 specifies the surface roughness and inorganic particle content of biaxially stretched polyester film. Patent Document 2 relates to crystalline biaxially stretched polyester film, and heat-shrinkable polyester film made from amorphous raw material and only uniaxially stretched differs from biaxially stretched polyester film in roughness due to surface protrusions and air escape condition when rolled. Therefore, an object of the present invention is to provide a heat-shrinkable polyester film that has good air release, good winding quality, is less prone to wrinkles, and has good printability even when it has a thickness of 15 μm to 50 μm. [Means for solving the problem]

[0005] The present invention, which has solved the above problems, comprises the following: 1. A heat-shrinkable polyester film characterized by satisfying the following requirements (1) to (5): (1) When the film is immersed in 90°C hot water for 10 seconds, the hot water heat shrinkage rate is 40% or more and 80% or less in the width direction of the film. (2) When the film is immersed in 90°C hot water for 10 seconds, the hot water heat shrinkage rate is between -5% and 10% in the longitudinal direction of the film. (3) The maximum projection height Sp of at least one film surface is 0.8 μm or more and 3.0 μm or less. (4) The arithmetic mean height Sa of at least one film surface is 0.03 μm or more and 0.2 μm or less. (5) The time required for air to escape between the front and back surfaces of the film is 14 seconds or less. 2. The heat-shrinkable polyester film according to 1., characterized in that the thickness of the film is 15 μm or more and 50 μm or less. 3. The heat-shrinkable polyester film according to 1 or 2, characterized in that the haze at a film thickness of 30 μm is 2% or more and 11% or less. 4. The heat-shrinkable polyester film according to any one of 1. to 3., which is a laminated heat-shrinkable polyester film having at least two layers laminated together. 5. A heat-shrinkable label using the heat-shrinkable polyester film described in any one of 1. to 4. 6. A package formed by covering at least a part of the outer periphery of an object to be packaged with the heat-shrinkable label described in 5. above and then heat-shrinking it. Effect of the Invention

[0006] The heat-shrinkable polyester film of the present invention maintains transparency and printability by controlling the surface roughness and air escape within a certain range, and even if the film thickness is thin, wrinkles and printability can be kept good when wound into a roll. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a diagram showing a method for measuring the air release time of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The heat-shrinkable polyester film of the present invention will be described in detail below. The method for producing the heat-shrinkable polyester film will be described in detail later, but the heat-shrinkable film is usually obtained by conveying and stretching the film using rolls or the like. In this case, the conveying direction of the film (film-forming direction) is referred to as the longitudinal direction, and the direction perpendicular to the longitudinal direction is referred to as the film width direction.

[0009] The heat-shrinkable polyester film of the present invention is a heat-shrinkable polyester film characterized by satisfying the following requirements (1) to (5): (1) When the film is immersed in 90°C hot water for 10 seconds, the hot water heat shrinkage rate is 40% or more and 80% or less in the width direction of the film. (2) When the film is immersed in 90°C hot water for 10 seconds, the hot water heat shrinkage rate is between -5% and 10% in the longitudinal direction of the film. (3) The maximum protrusion height Sp of at least one film surface is 0.8 μm or more and 3 μm or less. (4) The arithmetic mean height Sa of at least one film surface is 0.03 μm or more and 0.2 μm or less. (5) The time required for air to escape between the front and back surfaces of the film is 14 seconds or less.

[0010] The polyester used in the heat-shrinkable polyester film of the present invention is a polyester mainly composed of ethylene terephthalate units, which preferably account for 50 mol % or more, more preferably 60 mol % or more, and even more preferably 70 mol % or more of the 100 mol % of the polyester constituent units. Other dicarboxylic acid components constituting the polyester of the present invention include aromatic dicarboxylic acids such as isophthalic acid, orthophthalic acid, and 2,6-naphthalenedicarboxylic acid; aliphatic dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, and decanedicarboxylic acid; and alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid. It is also preferable that the polyester does not contain a polyvalent carboxylic acid having a valence of three or more (for example, trimellitic acid, pyromellitic acid, and anhydrides thereof, etc.). Heat-shrinkable polyester films obtained using polyesters containing such polyvalent carboxylic acids are difficult to achieve the required high shrinkage ratio.

[0011] Examples of diol components constituting the polyester include, in addition to ethylene glycol, aliphatic diols such as 1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-n-butyl-2-ethyl-1,3-propanediol, 2,2-isopropyl-1,3-propanediol, 2,2-di-n-butyl-1,3-propanediol, 1,4-butanediol, hexanediol, neopentyl glycol, and hexanediol; alicyclic diols such as 1,4-cyclohexanedimethanol; and aromatic diols such as bisphenol A. Among these, it is preferable to use a cyclic diol such as 1,4-cyclohexanedimethanol or a diol having 3 to 6 carbon atoms (for example, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, hexanediol, etc.). In particular, when 1,4-butanediol or neopentyl glycol is used, a polyester satisfying the essential requirements of the present invention is easily obtained.

[0012] In addition, the polyester has a total amorphous component of 100 mol% of the polyhydric alcohol component and 100 mol% of the polycarboxylic acid component in the entire polyester resin (i.e., a total of 200 mol%) of 17 mol% or more, preferably 18 mol% or more, more preferably 19 mol% or more, and particularly preferably 20 mol% or more. Among the above-mentioned monomer components, examples of monomers that can become amorphous components include neopentyl glycol, 1,4-cyclohexanedimethanol, isophthalic acid, 1,4-cyclohexanedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,2-diethyl-1,3-propanediol, 2-n-butyl-2-ethyl-1,3-propanediol, 2,2-isopropyl-1,3-propanediol, 2,2-di-n-butyl-1,3-propanediol, and hexanediol. The upper limit of the total amorphous component is not particularly limited, but it is preferably 30 mol% or less. By adjusting the amount of the amorphous component to fall within the above range, a polyester having a glass transition point (Tg) adjusted to 60 to 80° C. can be obtained.

[0013] It is preferable that the polyester does not contain a diol having 8 or more carbon atoms (e.g., octanediol, etc.) or a polyhydric alcohol having a valence of 3 or more (e.g., trimethylolpropane, trimethylolethane, glycerin, diglycerin, etc.). A heat-shrinkable polyester film obtained by using a polyester containing these diols or polyhydric alcohols is difficult to achieve a required high shrinkage rate. It is also preferable that the polyester does not contain diethylene glycol, triethylene glycol, or polyethylene glycol as much as possible.

[0014] Various additives, such as waxes, antioxidants, antistatic agents, crystal nucleating agents, viscosity reducers, heat stabilizers, coloring pigments, coloring inhibitors, and ultraviolet absorbers, may be added to the resin forming the heat-shrinkable polyester film of the present invention, as necessary.

[0015] It is preferable to add fine particles to the resin forming the heat-shrinkable polyester film of the present invention in order to set the maximum projection height Sp, the arithmetic mean height Sa, and the air escape time between the front and back surfaces of the film within a predetermined range on at least one of the film surfaces. Any fine particles can be selected, and examples of inorganic fine particles include silica, alumina, titanium dioxide, calcium carbonate, kaolin, barium sulfate, etc., and organic fine particles include acrylic resin particles, melamine resin particles, silicone resin particles, crosslinked polystyrene particles, etc. The average particle size of the fine particles is within the range of 1.0 to 5.0 μm (measured with a Coulter counter), and preferably within the range of 2.0 to 5.0 μm, and can be appropriately selected as necessary. The particle shape may be either spherical or amorphous, but spherical particles have more projections on the film surface than amorphous particles. However, spherical particles are generally more expensive than amorphous particles, so it is desirable to select them according to the purpose. The amount of fine particles added to the front and back layers of the heat-shrinkable polyester film is preferably 350 ppm or more and 20,000 ppm or less. If the amount of the fine particles added is less than 350 ppm, the maximum protrusion height Sp and the arithmetic mean height Sa on the film surface are low, and the air escape time cannot be within the specified range, which is not preferable. If the amount of the fine particles added is more than 20,000 ppm, the air escape time is shortened, which is preferable, but the maximum protrusion height Sp and the arithmetic mean height Sa are increased, which is not preferable, as they deteriorate the transparency and printability. More preferably, the amount of the fine particles added is 450 ppm or more and 19,000 ppm or less, and particularly preferably, the amount of the fine particles added is 550 ppm or more and 18,000 ppm or less. By using the above-mentioned preferred fine particles in combination with the preferred manufacturing method described below, protrusions suitable for the present invention can be formed on the film surface, and the maximum protrusion height Sp, arithmetic mean height Sa, and air escape time can be controlled within specified ranges.

[0016] The method of blending the above particles into the resin forming the heat-shrinkable polyester film can be, for example, addition at any stage of the production of the polyester resin, but it is preferable to add the particles as a slurry dispersed in ethylene glycol or the like at the stage of esterification or after the completion of the transesterification reaction and before the start of the polycondensation reaction, and proceed with the polycondensation reaction. It is also preferable to blend a slurry of the particles dispersed in ethylene glycol or water or the like with the polyester resin raw material using a vented kneading extruder, or to blend the dried particles with the polyester resin raw material using a kneading extruder.

[0017] The heat-shrinkable polyester film of the present invention may be subjected to corona treatment, coating treatment, flame treatment, or the like in order to improve the adhesiveness of the film surface. The heat-shrinkable polyester film of the present invention also includes a laminated polyester film having at least one polyester resin layer. When two or more polyester resin layers are laminated, the polyester resin layers may be polyesters of the same composition or different compositions. In addition, the layer that can be laminated as the other layer is not particularly limited as long as it is a thermoplastic resin layer, but is preferably a polystyrene resin layer in terms of cost and heat shrinkage properties. In the case of lamination of two or more layers of polyester resin layers only, it is necessary that the polyester resin layer containing fine particles is on the front and back sides. This is because the front and back layers overlap in the film roll form, and by setting the maximum protrusion height Sp and the arithmetic mean height Sa on the film surface within a predetermined range, wrinkles in the film roll can be suppressed. The layer structure may be one type two layers, two types three layers, three types three layers, or three types five layers, but a two type three layer structure is suitable for preventing the equipment from becoming large-sized and controlling the protrusions and transparency of the film surface. In the two type three layer structure, it is preferable to have a polyester resin layer containing fine particles / a polyester resin layer not containing fine particles / a polyester resin layer containing fine particles. By using the same polyester resin layer containing fine particles, there is an advantage that the protrusions on the front and back of the film can be controlled to be the same. In addition, by using a layer not containing fine particles as the intermediate layer, the transparency can be improved. In the two type three layer structure, it is preferable that the polyester resin layer containing fine particles on the front and back is 4% to 70% of the total thickness. If it is less than 4%, the thickness of one side of the polyester resin layer will be less than 2%, and if the thickness precision of the polyester resin layer containing fine particles during film production becomes poor, the thickness of the polyester resin layer containing fine particles will become thin and the desired surface protrusions will not be obtained, which is not preferable. There is no problem if it is higher than 70%, but if the polyester resin layer not containing fine particles becomes thick, it is not preferable because the transparency will deteriorate. In a two-kind three-layer structure, the thickness ratio of the polyester resin layer containing fine particles among the two types constituting the polyester resin layer containing fine particles / polyester resin layer not containing fine particles / polyester resin layer containing fine particles is more preferably 8% or more and 60% or less, and particularly preferably 10% or more and 50% or less.

[0018] It is preferable to add a thermoplastic resin and / or a rubber component to the polystyrene resin. Examples of the thermoplastic resin include styrene resins such as polystyrene having an atactic structure, AS resin, and ABS resin, polyester resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polyamide resins such as nylon 6, nylon 66, nylon 12, nylon 4, and polyhexamethylene adipamide, and polyolefin resins such as polyethylene, polypropylene, and polybutene.

[0019] On the other hand, as the rubber component, a rubber-like copolymer containing a styrene-based compound as its constituent component is preferred, and examples thereof include random, block or graft copolymers obtained by copolymerizing one or more types of styrene and rubber components. Examples of such rubber-like copolymers include styrene-butadiene copolymer rubber, styrene-isoprene block copolymer, rubbers in which the butadiene portion of these is partially or entirely hydrogenated, methyl acrylate-butadiene-styrene copolymer rubber, acrylonitrile-butadiene-styrene copolymer rubber, acrylonitrile-alkyl acrylate-butadiene-styrene copolymer rubber, and methyl methacrylate-alkyl acrylate-butadiene-styrene copolymer rubber. The rubber-like copolymer containing the above-mentioned styrene-based compound as its constituent component has a styrene unit, and therefore has good dispersibility in polystyrene-based resins having a syndiotactic structure, and has a large effect of improving the plasticity of polystyrene-based resins. In addition, as the compatibility adjuster, the above-mentioned rubber-like copolymer containing the above-mentioned styrene-based compound as its constituent component can be suitably used.

[0020] On the other hand, as the rubber component, other usable materials include natural rubber, polybutadiene, polyisoprene, polyisobutylene, neoprene, ethylene-propylene copolymer rubber, urethane rubber, silicone rubber, acrylic rubber, polyether-ester rubber, polyester-ester rubber, and the like.

[0021] The weight-average molecular weight of the polystyrene resin is preferably 10,000 or more, more preferably 50,000 or more. A weight-average molecular weight of less than 10,000 is not preferred because the strength and elongation properties and heat resistance of the film tend to decrease. There is no particular upper limit to the weight-average molecular weight, but a weight-average molecular weight of more than 1,500,000 is not preferred because breakage may occur due to an increase in the stretching tension. Polystyrene resins are commercially available in various grades from various manufacturers, and commercially available ones may be used. The other layer may be one layer or two or more layers. In the case of multilayers with polystyrene, it is recommended to have a polyester layer / polystyrene layer / polyester layer from the film surface, with the polyester layer having excellent gloss and printability as the outermost layer. However, since polyester and polystyrene are incompatible resins, there is a problem of relative peeling. Therefore, it is preferable to have a 3-type 5-layer structure with adhesive layers sandwiched between the film surface: polyester layer / adhesive layer / polystyrene layer / adhesive layer / polyester layer. A 3-type 7-layer structure or a 3-type 9-layer structure is also acceptable, but the equipment required is larger than that for a 3-type 5-layer structure.

[0022] In the three-kind, five-layer film, the polyester layer is preferably 20% to 80% of the total thickness. If it is less than 20%, the thickness of one side of the polyester layer is less than 10%, which is not preferred because the printability and gloss of the film will be insufficient. If it is more than 80%, the polystyrene layer will become thin and the effect of suppressing the shrinkage rate in the longitudinal direction will be small, which is not preferred. In the three-kind, five-layer film, the polyester layer is more preferably 25% to 75% of the total thickness, and particularly preferably 30% to 70%.

[0023] In the case of a three-kind, five-layer structure, the adhesive layer is preferably 1% to 14% of the total thickness. If it is less than 1%, the adhesiveness decreases, which is not preferred. If it is more than 14%, the thickness of the polyester layer and the polystyrene layer becomes thin, which is not preferred, as the heat shrinkage properties decrease. In the case of a three-kind, five-layer structure, the adhesive layer is more preferably 2% to 12% of the total thickness, and particularly preferably 3% to 10%. In the 3-kind 5-layer film, the polystyrene layer is preferably 20% to 80% of the total thickness. If it is less than 20%, the effect of suppressing the shrinkage rate in the longitudinal direction becomes small, which is not preferred. If it is 80% or more, the thickness of one side of the polyester layer becomes less than 10%, which is not preferred because the printability and gloss of the film are insufficient. In the 3-kind 5-layer film, the polystyrene layer is more preferably 25% to 75% of the total thickness, and particularly preferably 30% to 70%.

[0024] It is preferable that the heat-shrinkable polyester film of the present invention, when treated in 90°C hot water for 10 seconds under no load, has a heat shrinkage rate in the width direction, which is the main shrinkage direction of the film, calculated from the lengths before and after shrinkage using the following formula 1 (i.e., the hot water heat shrinkage rate at 90°C) of 40% or more and 80% or less. Heat shrinkage rate = {(length before shrinkage - length after shrinkage) / length before shrinkage} × 100 (%) Formula 1

[0025] If the hot water shrinkage rate in the main shrinkage direction at 90°C is less than 40%, when the film is used for beverage labels or lunch box packaging, the shrinkage amount is small, which is undesirable because it causes label wrinkles and sagging after heat shrinkage. The hot water shrinkage rate at 90°C is more preferably 43% or more, particularly preferably 46% or more, and most preferably 50% or more. There is no problem if the hot water heat shrinkage rate in the main shrinkage direction at 90°C is higher than 80%, but in the present invention, it was not possible to obtain a film with a hot water heat shrinkage rate at 90°C of higher than 80%, so the upper limit was set at 80%.

[0026] The heat-shrinkable polyester film of the present invention preferably has a hot water shrinkage rate at 90°C in the longitudinal direction perpendicular to the main shrinkage direction of -5% or more and 10% or less. If the hot water shrinkage rate at 90°C in the longitudinal direction is less than -5%, when used for beverage labeling, the label stretches and the label height on the PET bottle increases, which is undesirable. The hot water shrinkage rate at 90°C in the longitudinal direction is more preferably -4% or more, and particularly preferably -3% or more. If the hot water shrinkage rate at 90°C in the longitudinal direction is more than 10%, when used for beverage labeling, the label will shrink and the label height on the PET bottle will be shortened, which is undesirable. It may also cause distortion of the label after shrinkage. The hot water shrinkage rate at 90°C in the longitudinal direction is more preferably 9% or less, even more preferably 8% or less, particularly preferably 7% or less, and most preferably 6% or less.

[0027] The maximum projection height Sp on at least one surface of the heat-shrinkable polyester film of the present invention is preferably 3.0 μm or less, more preferably 2.5 μm or less, and even more preferably 2.0 μm or less. If the maximum projection height Sp is more than 3.0 μm, the formation of coarse projections can cause printing defects, resulting in poor print appearance and poor design, which is undesirable as it impairs the film quality. The maximum projection height Sp on at least one surface of the heat-shrinkable polyester film of the present invention is preferably 0.8 μm or more, more preferably 1.2 μm or more, and even more preferably 1.6 μm or more. If the maximum projection height Sp is less than 0.8 μm, the air entrained during winding into a roll is not uniformly removed, and poor appearance such as wrinkles and pimples on air bubbles is likely to occur, and winding properties are likely to deteriorate.

[0028] The arithmetic mean height Sa of at least one surface of the heat-shrinkable polyester film of the present invention is preferably 0.2 μm or less, more preferably 0.18 μm or less, and even more preferably 0.16 μm or less. If the arithmetic mean height Sa is more than 0.2 μm, the film surface may become rough, which may impair transparency or deteriorate printability. The arithmetic mean height Sa of at least one surface of the heat-shrinkable polyester film of the present invention is preferably 0.03 μm or more, more preferably 0.035 μm or more, and even more preferably 0.04 μm or more. If the arithmetic mean height Sa is less than 0.03 μm, the air entrained during winding into a roll is not uniformly removed, and poor appearance such as wrinkles and pimples on air bubbles is likely to occur, and winding properties are likely to deteriorate.

[0029] The air escape time between the front and back surfaces of the heat-shrinkable polyester film of the present invention is preferably 14 seconds or less, more preferably 13 seconds or less, even more preferably 12 seconds or less, and particularly preferably 10 seconds or less. If the air escape time exceeds 14 seconds, the air wound into the roll will not be uniformly escaped during the production process and when the film is wound into a roll by rewinding, slitting, etc., which is likely to cause poor appearance such as wrinkles and air bubble-like pimples.

[0030] The heat-shrinkable polyester film of the present invention has a haze of 11% or less at a film thickness of 30 μm, more preferably 9% or less, even more preferably 7% or less, and particularly preferably 5% or less. If the haze exceeds 11% at a film thickness of 30 μm, the print appearance deteriorates and it becomes difficult to detect foreign matter during high-speed processing, making it difficult to obtain sufficient quality.

[0031] The thickness of the heat-shrinkable polyester film of the present invention is preferably 15 μm or more and 50 μm or less. If the film thickness is less than 15 μm, the stiffness of the film is significantly reduced, and the roll is likely to wrinkle, which is not preferable. On the other hand, even if the film thickness is thick, there is no problem as a film roll, but it is preferable to make the film thinner from the viewpoint of cost and environment. The thickness of the film is more preferably 17 μm or more and 45 μm, and particularly preferably 20 μm or more and 40 μm.

[0032] The heat-shrinkable polyester film of the present invention can be obtained by melt-extruding the above-mentioned polyester raw material with an extruder to form an unstretched film, and then uniaxially stretching the unstretched film in the transverse direction and heat-treating it by a predetermined method described below. When laminating, multiple extruders, feed blocks, and multi-manifolds can be used. The polyester can be obtained by polycondensing the above-mentioned suitable dicarboxylic acid component and diol component by a known method. In addition, usually, two or more kinds of chip-like polyesters are mixed and used as the raw material for the film. When laminating, multiple extruders can be used.

[0033] When melt extruding the raw resin, it is preferable to dry the polyester raw material using a dryer such as a hopper dryer or a paddle dryer, or a vacuum dryer. After drying the polyester raw material in this way, it is melted at a temperature of 200 to 300°C and extruded into a film using an extruder. For extrusion, any existing method such as a T-die method or a tubular method can be used. The extruded sheet-like molten resin can then be quenched to obtain an unstretched film. As a method for quenching the molten resin, a method in which the molten resin is cast from a die onto a rotating drum and rapidly cooled and solidified to obtain a substantially unoriented resin sheet can be suitably adopted.

[0034] Furthermore, the obtained unstretched film can be stretched in the width direction under predetermined conditions as described below to obtain the heat-shrinkable polyester film of the present invention. Preferred stretching for obtaining the heat-shrinkable polyester film of the present invention will be described below. By adopting the preferred stretching method and conditions described below, the film surface state suitable for the present invention can be formed.

[0035] Ordinary heat-shrinkable polyester films are produced by stretching an unstretched film in the direction in which it is desired to shrink. Alternatively, there is a biaxial stretching method in which the film is stretched longitudinally and then stretched transversely, but biaxial stretching requires large-scale equipment. In the present invention, the film is uniaxially stretched in the width direction, which is the main shrinkage direction. The production method using uniaxial stretching in the width (transverse) direction has the advantage that it can be produced with simple equipment since no equipment for stretching in the longitudinal direction is used.

[0036] For widthwise stretching, the unstretched film is introduced into a tenter device that can heat the film by holding both ends of the film with clips, and the film is heated to a predetermined temperature with hot air. The film is then stretched by increasing the distance between the clips while transporting it in the longitudinal direction. The preheating temperature of the unstretched film is preferably Tg+10°C or more +80°C or less. More preferably, it is Tg+20°C or more +60°C or less. If it is less than Tg+10°C, the preheating temperature is insufficient, which increases the stretching force and makes the film more likely to break, which is not preferred. Furthermore, if the film is heated at a temperature higher than Tg+80°C, the stretching force in the width direction of the unstretched sheet decreases, which leads to poor thickness accuracy in the width direction (uneven thickness), which is not preferred. More preferably, it is Tg+30 or more +50°C or less.

[0037] The film temperature during width direction stretching is preferably Tg°C or more and Tg+30°C or less. If the film temperature is lower than Tg, the stretching force becomes too high, which is undesirable as the film is more likely to break. If the film temperature exceeds Tg+30°C, the stretching force is too low, which is undesirable as the thermal shrinkage in the width direction measured at 90°C as described above becomes low. More preferably, the film temperature is Tg+3°C or more and +25°C or less, and even more preferably, Tg+5°C or more and +20°C or less.

[0038] The stretching ratio in the width direction is preferably 3.5 times or more and 6 times or less. If the stretching ratio is less than 3.5 times, the stretching force is insufficient, and the thickness accuracy in the width direction of the film (so-called uneven thickness) is deteriorated. If the stretching ratio exceeds 6 times, the risk of breakage during film production increases and the equipment becomes long, which is not preferable. More preferably, it is 3.7 times or more and 5.5 times or less. Although not particularly limited, heat treatment may be performed after the width direction stretching to adjust the shrinkage rate. The film temperature during heat setting is preferably not less than the width direction film stretching temperature and not more than the width direction film stretching temperature + 30 ° C. If the film heat setting temperature is less than the width direction film stretching temperature, molecular relaxation in the width direction becomes insufficient and there is no effect of heat setting, which is not preferable. If the film heat setting temperature exceeds the width direction film stretching temperature + 30 ° C., the film crystallizes and the shrinkage rate decreases, which is not preferable. More preferably, it is the film stretching temperature in the width direction +1°C or more and the film stretching temperature in the width direction +25°C or less, and even more preferably, it is the film stretching temperature in the width direction +2°C or more and the film stretching temperature in the width direction +20°C or less.

[0039] The heat-shrinkable polyester film of the present invention can be made into a label by a conventionally known method. As an example, a heat-shrinkable polyester film cut to a desired width is appropriately printed, and the left and right ends of the film are overlapped and joined by solvent bonding or the like to produce a tube film. This tube film is cut to an appropriate length to produce a tube-shaped label. As an organic solvent for adhesion, cyclic ethers such as 1,3-dioxolane or tetrahydrofuran are preferred. In addition, aromatic hydrocarbons such as benzene, toluene, xylene, and trimethylbenzene, halogenated hydrocarbons such as methylene chloride and chloroform, phenols such as phenol, and mixtures thereof can be used.

[0040] After perforations are formed in the label by a known method, it is placed on a PET bottle, and the PET bottle is placed on a belt conveyer or the like and passed through a shrink tunnel that blows steam (steam tunnel) or a shrink tunnel that blows hot air (hot air tunnel). The label thermally shrinks when passing through these tunnels, and the label is attached to the bottle container such as a PET bottle.

[0041] The packaging body of the present invention is formed by covering at least a part of the outer periphery of the packaging object with a label having a perforation or a notch obtained from the heat-shrinkable polyester film of the present invention and heat-shrinking it. Examples of the packaging object include PET bottles for beverages, various bottles, cans, plastic containers for sweets and lunch boxes, and paper boxes. In addition, when the label obtained from the heat-shrinkable polyester film is heat-shrunk to cover the packaging object, the label is usually heat-shrunk by about 5 to 70% to be adhered to the packaging body. In addition, the label to be covered on the packaging object may or may not be printed. EXAMPLES

[0042] Next, the present invention will be specifically described using examples and comparative examples, but the present invention is not limited to the embodiments of these examples and can be appropriately modified within the scope of the present invention. The film evaluation method is shown below.

[0043] [Heat shrinkage rate (hot water heat shrinkage rate)] The film was cut into a 10cm x 10cm square and placed in warm water at 90℃±0.5℃ with no load. After immersing it in water at 25℃±0.5℃ for 10 seconds to allow it to shrink, The film was pulled out from the inside, and the dimensions in the longitudinal (vertical) and transverse (horizontal) directions of the film were measured, and the thermal shrinkage rate of each direction was calculated according to the following formula (1). The direction with the largest thermal shrinkage rate was determined as the main shrinkage direction. Heat shrinkage rate = {(length before shrinkage - length after shrinkage) / length before shrinkage} x 100 (%) Formula (1)

[0044] [Arithmetic mean height Sa, maximum height Sp] In accordance with ISO25178, a piece measuring 10cm in the longitudinal direction and 10cm in the transverse direction was cut from the obtained film, and scanned using a Zygo white laser interferometer (NEW VIEW8300) under the following observation conditions to measure the arithmetic mean height Sa (μm) and maximum projection height Sp (μm). The measurement was performed on the surface excluding foreign matter such as unmelted material and dust. Measurements were taken at 10 randomly selected points on a 10 cm x 10 cm sample, and the average values ​​were taken as the arithmetic mean height Sa and the maximum projection height Sp, respectively. (Observation conditions) Objective lens: 10x Zoom lens: 1x Field of view: 0.82 x 0.82 mm Sampling interval: 0.803μm Estimated measurement time: 4 seconds Type: Surface Mode: CSI Z resolution: High Scan length: 20μm Camera mode: 1024×1024@100Hz Shutter speed: 100% Light output: 1.3% Option: SureScan Off SmartPsi Averages 4 Noise Reduction Signal processing option: Fringe order analysis Advanced Fringe removal ON

[0045] [Air release time] As shown in Figure 1, film 4 is placed on base plate 1. Next, film holder 2 is placed on top of film 4 and fixed in place to apply tension to film 4. Next, film 5 is placed on top of film holder 2 with the side opposite to the top surface of film 4 placed on base plate 1 facing down. Next, film holder 8 is placed on top of film 5, and the film holders 8, 2 and base plate 1 are fixed in place using screws 3. Next, cavity 2a in film holder 2 is connected to vacuum pump 6 via small hole 2c in film holder 2 and pipe 7. When vacuum pump 6 is driven, film 5 is sucked into cavity 2a and tension is applied to it. At the same time, the pressure in the overlapping surfaces of films 4 and 5 is reduced via small hole 2d provided circumferentially in film holder 2, and films 4 and 5 begin to adhere to each other from the outer periphery at their overlapping surfaces. The state of adhesion can be easily confirmed by observing the interference fringes from above the overlapping surfaces. Then, the time (seconds) from when interference fringes appear on the periphery of the overlapping surfaces of films 4 and 5 until they spread to the front of the overlapping surfaces and stop moving is measured, and this time (seconds) is taken as the air release time. The measurement is repeated five times by replacing the two films, and the average value is used.

[0046] [Film thickness] The measurement was performed using a dial gauge in accordance with JIS K7130-1999 Method A.

[0047] [Film Haze] In accordance with JIS K7361-1, the film was cut into a square shape with each side being 10 cm long, and the haze was measured using a haze meter NDH2000 manufactured by Nippon Denshoku Co., Ltd. Measurements were performed at three locations, and the average value was taken as the actual haze measurement value, and the haze converted into 30 μm was calculated using the following formula (2). Haze = measured haze value × 30 / film thickness (% / 30μm) Formula (2)

[0048] [Tg (glass transition temperature)] Tg was determined according to JIS-K7121-1987 using a differential scanning calorimeter (model: DSC220) manufactured by Seiko Electronics Co., Ltd. In detail, 10 mg of unstretched film was heated from -40°C to 120°C at a heating rate of 10°C / min, and an endothermic curve was measured. Tangent lines were drawn before and after the inflection point of the obtained endothermic curve, and the intersection point was determined as the glass transition point (Tg; °C).

[0049] [Intrinsic viscosity (IV)] 0.2 g of polyester was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (weight ratio)), and the viscosity was measured using an Ostwald viscometer at 30° C. The unit is dl / g.

[0050] [Composition analysis] Each sample was dissolved in a solvent in which chloroform D (manufactured by Eurisopp) and trifluoroacetic acid D1 (manufactured by Eurisopp) were mixed at a volume ratio of 10:1 to prepare a sample solution, and the NMR of the protons in the sample solution was measured using an NMR "GEMINI-200" (manufactured by Varian) at a temperature of 23°C and an accumulation number of 64. In the NMR measurement, the peak intensity of a specified proton was calculated, and the amount of the component in 100 mol% of the diacid component and the amount of the component in 100 mol% of the polyhydric alcohol component were measured.

[0051] [Shrinkage finish] The ends of the heat-shrinkable film were welded with an impulse sealer (manufactured by Fuji Impulse Co., Ltd.) to obtain a cylindrical label with the width direction as the circumferential direction. In addition, 0.5 mm holes were made in the longitudinal direction of the film at 3 mm pitches. In addition, 0.5 mm holes were made in the longitudinal direction of the film at intervals of 10 mm in the width direction of the film at 3 mm pitches (so-called perforations to make the label easy to peel off). The diameter of the label in the shrink direction was 68 mm. This label was placed on a commercially available 500 ml PET bottle (containing contents; body diameter 62 mm, minimum diameter of neck 25 mm) and heat-shrunk by passing it through steam using a steam tunnel (model: SH-1500-L) manufactured by Fuji Astec Inc. adjusted to 90°C (tunnel passing time: 5 seconds). The shrink finish of the label was visually evaluated according to the following criteria. It was visually evaluated on a 5-point scale according to the following criteria. The defects described below include jumping up, wrinkles, insufficient shrinkage, folded label edges, whitening from shrinkage, etc. A rating of 3 or more was considered to be acceptable. 5: Best finish (no defects) 4: Good finish (one defect) 3: There are two defects 2: 3 to 5 defects 1: Many defects (6 or more)

[0052] [Evaluation of wrinkles on film rolls] The heat-shrinkable polyester film thus formed was wound up to a width of 500 mm and a length of 1000 m, and the wrinkles on the surface of the roll were visually evaluated according to the following criteria. ○: No wrinkles △: There are slight wrinkles, but the wrinkles disappear when a tension of about 20 N / m is applied to the pulled-out film. ×: There are strong wrinkles, and the wrinkles do not disappear even when a tension of about 20 N / m is applied to the pulled-out film.

[0053] [Printability evaluation] A film roll with a width of 500 mm and a length of 1000 m was printed (one-color printing) using grass green ink from Toyo Ink Mfg. Co., Ltd. The thickness of the ink after printing was 1 μm. The area of ​​each measurement on the printed film was 900 mm2 The print dot dropout was investigated using a magnifying glass with a magnification of 5x (30mm in the longitudinal direction, 30mm in the transverse direction). Measurements were taken at three arbitrary points in the transverse direction of the printed roll. In addition, measurements were taken at three points in the transverse direction (total of six points) at a position 50m away in the longitudinal direction from the position where the measurement was taken in the transverse direction, and the area was measured at 900mm. 2 The length (30 mm in the longitudinal direction, 30 mm in the transverse direction) was measured using a 5x magnification loupe, and a rating of ○ or △ was considered pass. ○: Missing dots are less than 1% △: Missing dots are between 1% and 3% ×: Missing dots are 3% or more

[0054] [Preparation of polyester raw materials] In a stainless steel autoclave equipped with a stirrer, a thermometer, and a partial reflux condenser, 100 mol % of dimethyl terephthalate (DMT) as a dibasic acid component and 100 mol % of ethylene glycol (EG) as a glycol component were charged so that the molar ratio of glycol was 2.2 times that of methyl ester, and 0.05 mol % (relative to the acid component) of zinc acetate was used as an ester exchange catalyst to carry out an ester exchange reaction while distilling off the produced methanol outside the system. Then, 0.025 mol % (relative to the acid component) of antimony trioxide was added as a polycondensation catalyst, and a polycondensation reaction was carried out at 280°C under reduced pressure of 26.6 Pa (0.2 Torr), obtaining a polyester (A) with an intrinsic viscosity of 0.75 dl / g. This polyester is polyethylene terephthalate.

[0055] During production, SiO2 was added as a lubricant at a ratio of 8,000 ppm to the polyester to polyesters B1 to B8, and the intrinsic viscosity was 0.75 dl / g. The SiO2 of each polyester was spherical in shape and had a weight average particle size of 1 μm for polyester B1, irregular in shape and had a weight average particle size of 1.5 μm for polyester B2, irregular in shape and had a weight average particle size of 2 μm for polyester B3, irregular in shape and had a weight average particle size of 2.5 μm for polyester B4, irregular in shape and had a weight average particle size of 3 μm for polyester B5, irregular in shape and had a weight average particle size of 4 μm for polyester B6, irregular in shape and had a weight average particle size of 5 μm for polyester B7, and irregular in shape and had a weight average particle size of 6 μm for polyester B8.

[0056] In addition, polyesters (C, D, E) shown in Table 1 were synthesized by the same method as above. In the table, NPG is neopentyl glycol, CHDM is 1,4-cyclohexanedimethanol, and BD is 1,4-butanediol. The intrinsic viscosities of polyesters C, D, and E were 0.75 dl / g, 0.75 dl / g, and 1.15 dl / g, respectively. Each polyester was appropriately cut into chips.

[0057] The details of the raw material chips used in the Examples and Comparative Examples, the resin compositions of the films in the Examples and Comparative Examples, and the layer structures and manufacturing conditions are shown in Tables 1 and 2. Hereinafter, Examples 1 to 6 will be read as Reference Examples 1 to 6, and Examples 8 and 9 as Reference Examples 8 and 9, respectively.

[0058] [Table 1]

[0059] [Table 2]

[0060] Example 1 Using the co-extrusion method, the resin for forming the core layer and the resin for forming the skin layer were melt-extruded from separate extruders (first and second extruders), laminated in a die (T-die), and quenched by winding around a rotating metal roll cooled to a surface temperature of 30°C, to obtain an unstretched film having a thickness of 138 μm and a two-kind three-layer structure, i.e., a structure in which the skin layer was laminated on the outside of the core layer. At this time, the above-mentioned polyester A, polyester C, and polyester E were mixed in a weight ratio of 20:70:10 for the core layer and fed into the extruder. This mixed resin was melted at 260°C. On the other hand, the above-mentioned polyester A, polyester B3, polyester C, and polyester E were mixed in a weight ratio of 12:8:70:10 for the skin layer and fed into the extruder. This mixed resin was melted at 260°C. At this time, the thickness ratio of the skin layer / core layer / skin layer was 1:2:1. The take-up speed of the unstretched film (the rotation speed of the metal roll) was about 30 m / min, and the Tg of the unstretched film was 69°C. The unstretched film obtained was introduced into a tenter (transverse stretching machine). The temperature in the preheating step was 95°C (Tg+26°C), and the temperature in the stretching step was 78°C (Tg+9°C), and the film was stretched 4.6 times. The film after the transverse stretching was heat-treated in a tensioned state at 83°C (stretching temperature+5°C) for 8 seconds. Thereafter, the film was cooled, both edges were cut and removed, and the film was wound into a roll with a width of 800 mm, thereby continuously producing a stretched film with a thickness of 30 μm over a length of 2000 m. The properties of the obtained film were evaluated by the above-mentioned method. The evaluation results are shown in Table 3. The film had good wrinkle and shrink finish properties in the film roll.

[0061] Example 2 A film having a thickness of 30 μm was prepared in the same manner as in Example 1, except that Polyester B3 was changed to Polyester B4. The evaluation results are shown in Table 3. The air removal time was shorter than in Example 1, and the film had good wrinkles in the film roll and good shrink finish.

[0062] Example 3 A film having a thickness of 30 μm was prepared in the same manner as in Example 1, except that Polyester B3 was changed to Polyester B5. The evaluation results are shown in Table 3. The air release time was shorter than in Example 1, and the film had good wrinkles in the film roll and good shrink finish.

[0063] Example 4 A film having a thickness of 30 μm was prepared in the same manner as in Example 1, except that Polyester B3 was changed to Polyester B6. The evaluation results are shown in Table 3. The air removal time was shorter than in Example 1, and the haze was slightly higher, but the film had good wrinkles in the film roll and good shrink finish.

[0064] Example 5 A film having a thickness of 30 μm was prepared in the same manner as in Example 1, except that Polyester B3 was changed to Polyester B7. The evaluation results are shown in Table 3. The air removal time was shorter than in Example 1, and the haze was slightly higher, but the film had good wrinkles in the film roll and good shrink finish.

[0065] Example 6 A film having a thickness of 30 μm was prepared in the same manner as in Example 1, except that the raw material of the core layer in Example 1 was changed to the same raw material as the skin layer and the layer was changed to one type of three. The evaluation results are shown in Table 3. The haze was slightly high, but the film had good wrinkle and shrink finish properties in the film roll.

[0066] Example 7 Using the co-extrusion method, the resin for forming the core layer, the resin for forming the skin layer, and the resin for forming the adhesive layer were melt-extruded from separate extruders (first to third extruders), laminated in a die (T-die), and quenched by winding around a rotating metal roll cooled to 30°C by the air knife method to obtain an unstretched film (polystyrene-based resin laminated sheet) having a thickness of 138 μm and a three-kind five-layer structure, that is, an intermediate layer (adhesive layer) was laminated on both sides of the core layer, and a skin layer was laminated on the outside of each of the intermediate layers. The method of forming each layer of the unstretched film (process up to melt extrusion) is as follows. In the following description, the first layer, second layer, third layer, fourth layer, and fifth layer are referred to in order from the front and back of the polystyrene-based mixed resin laminated sheet (i.e., the surface of the fifth layer is the surface in contact with the metal roll). The take-up speed of the unstretched film (rotation speed of the metal roll) was about 30 m / min. · Formation of the first and fifth layers (skin layers) The dried polyester A, polyester B4, polyester C, and polyester E were mixed in a ratio of 12:8:70:10 and fed into the first extruder. This mixed resin was melt extruded at 260°C (melt extruded so as to be laminated on the outside of the intermediate layer laminated on the outside of the front and back of the core layer). In order to stabilize the extrusion from the T-die, a helical-type and parallel-type gear pump was interposed between the extruder and the T-die. · Formation of the second and fourth layers (adhesive layers) The chips F described above were pre-dried using a blender device, and the pre-dried chips F were continuously fed to a hopper immediately above the second extruder using a fixed-volume screw feeder. The fed chips D were then melt-extruded from the T-die of the second extruder (melt-extruded so as to be laminated on the outside of the front and back of the core layer). The temperature of the second extruder was adjusted to 200°C. In addition, in order to stabilize the extrusion from the T-die, a helical-type and parallel-type gear pump was interposed between the extruder and the T-die, as in the case of the extrusion from the first extruder. · Formation of the third layer (core layer) The chips G, H, and I were pre-dried using a blender, and then fed into the third extruder in a mixing ratio of 43:43:14. The mixed resin was melt-extruded at 200°C. In addition, in order to stabilize the extrusion from the T-die, a helical-type and parallel-type gear pump was interposed between the extruder and the T-die, as in the case of the extrusion from the first extruder and the second extruder. In extruding the resin using each of the above extruders, the output rates of the first to third extruders in forming the unstretched film were adjusted so that the thicknesses of the first layer / second layer / third layer / fourth layer / fifth layer were 23 / 3 / 48 / 3 / 23. A film having a thickness of 30 μm was produced from the obtained unstretched film in the same manner as in Example 1, except that the stretching temperature in the width direction was changed to 82° C. The evaluation results are shown in Table 3. The film had good wrinkles in the film roll and good shrink finish.

[0067] Example 8 A film having a thickness of 30 μm was prepared in the same manner as in Example 1, except that polyester C was changed to polyester D. The Tg of the unstretched film was 69° C. The evaluation results are shown in Table 3. The film had good wrinkles and shrink finish in the film roll.

[0068] Example 9 Polyester B3 was changed to Polyester B1, and the raw materials for the skin layer were Polyester A, Polyester B1, Polyester C, and Polyester E in a weight ratio of 4 / 16 / 70 / 10. A film having a thickness of 30 μm was obtained in the same manner as in Example 1, except that in the process of stretching the unstretched film in the width direction, the temperature of the preheating process was changed to 100° C., the temperature of the stretching process was changed to 85° C., and the heat treatment temperature was changed to 86° C. The evaluation results are shown in Table 3. The film had good wrinkles in the film roll and good shrinkage finish.

[0069] Comparative Example 1 A film having a thickness of 30 μm was prepared in the same manner as in Example 1, except that Polyester B3 was changed to Polyester B1. The evaluation results are shown in Table 3. The air release time was longer than in Example 1, and wrinkles in the film roll were noticeable.

[0070] Comparative Example 2 A film having a thickness of 30 μm was prepared in the same manner as in Example 1, except that Polyester B3 was changed to Polyester B2. The evaluation results are shown in Table 3. The air release time was longer than in Example 1, and wrinkles in the film roll were noticeable.

[0071] Comparative Example 3 A film having a thickness of 30 μm was prepared in the same manner as in Example 1, except that Polyester B3 was changed to Polyester B8. The evaluation results are shown in Table 3. The air release time was short and wrinkles were good, but the maximum projection height Sp of the film surface and the arithmetic mean height of the film surface were high, so there were missing dots during printing, and the film had poor printability.

[0072] Comparative Example 4 A film having a thickness of 30 μm was prepared in the same manner as in Example 9, except that in the process of stretching the unstretched film in the width direction, the temperature in the preheating step was changed to 95° C., the width direction stretching temperature was changed to 83° C., and the heat treatment temperature was changed to 88° C. The evaluation results are shown in Table 3. The air removal time was longer than in Example 1, and the film had noticeable wrinkles in the film roll.

[0073] Comparative Example 5 A film having a thickness of 30 μm was obtained in the same manner as in Example 1, except that in the process of stretching the unstretched film in the width direction from Example 1, the preheating step and stretching step were changed to 76° C. (Tg+7° C.) and the heat treatment temperature was changed to 88° C. The evaluation results are shown in Table 3. The air release time was longer than in Example 1, and the film had noticeable wrinkles in the film roll. This is thought to be due to the fact that the stretching stress during film stretching was high, making the lubricant more likely to be crushed.

[0074] [Table 3] [Industrial Applicability]

[0075] The heat-shrinkable polyester film of the present invention has a high heat shrinkage rate, is excellent in transparency and printability, and has a short air release time, so that a film roll with a good appearance can be obtained. [Explanation of symbols]

[0076] 1. Base board 2,8.Film holder 2a.Slot hole 3. Screws 4.5. Film 6. Vacuum pump 7. Pipes X. Film overlap

Claims

1. A laminated heat-shrinkable film having a polyester resin layer containing 350 ppm or more and 20,000 ppm or less of fine particles having an average particle size of 1.0 μm or more and 5.0 μm or less on at least the front and back surfaces, and having a polystyrene resin layer as an intermediate layer, the laminated heat-shrinkable film being characterized in that it satisfies the following requirements (1) to (6). (1) When the film is immersed in 90°C hot water for 10 seconds, the hot water heat shrinkage rate is 40% or more and 80% or less in the width direction of the film. (2) When the film is immersed in 90°C hot water for 10 seconds, the hot water heat shrinkage rate is -5% or more and 10% or less in the longitudinal direction of the film. (3) The maximum projection height (Sp) of at least one of the film surfaces is 0.8 μm or more and 3.0 μm or less. (4) The arithmetic mean height Sa of at least one of the film surfaces is 0.03 μm or more and 0.2 μm or less. (5) The time required for air to escape between the front and back surfaces of the film is 12 seconds or less. (6) The thickness of the film is 30 μm or more and 50 μm or less.

2. 2. The laminated heat shrinkable film according to claim 1, wherein the haze at a film thickness of 30 μm is 2% or more and 11% or less.

3. 3. The laminated heat-shrinkable film according to claim 1, which is a laminated heat-shrinkable film comprising at least two polyester-based film layers laminated together.

4. A heat-shrinkable label using the laminated heat-shrinkable film according to any one of claims 1 to 3.

5. A package formed by covering at least a part of the outer periphery of an object to be packaged with the heat-shrinkable label according to claim 4 and then heat-shrinking the label.

Citation Information

Patent Citations

  • Heat-shrinkable polyester film roll

    JP2019199570A

  • Heat-shrinkable polyester film, process for production thereof, and package

    WO2008026530A1

  • Malleable conductive paste and method for producing curved printed circuit board

    WO2017170496A1

  • Low adsorption sealant film, layered body, and packaging bag

    WO2020071315A1

  • Radiation temperature measuring device

    JP1977040387A